Enhancing Nursing Practice Through Mindfulness: A Systematic Review of Emotional Intelligence-Based Interventions and Their Outcomes - Mhalkar, Vithoba Narayan; Bhore, Nilima Rajan (Journal of Neonatal Surgery, 2025)
Background: The growing prevalence of stress and burnout among nurses is a persistent issue that affects not only healthcare workers but also the quality and safety of patient care. Addressing this challenge requires a multi-level approach involving organizational support, personal coping mechanisms, and systemic reforms in healthcare workforce management. There is a clear need for more integrative research and interventions targeting emotional, communicative, and resilience-based competencies among nurses. Programs such as the Mindfulness-Based Stress Reduction (MBSR) and peer support initiatives have shown promise in improving nurses' psychological well-being. Methods and materials: The researcher discovered 108 papers using electronic search engines, unpublished publications, and published articles evaluated by Google Scholar, PubMed, Research Gate, and Scopus, which were searched for articles published between 2011 and 2025. After a careful examination of most of these publications, the main study key terms were mindfulness, emotional intelligence, job satisfaction, interpersonal communication, and resilience among nurses, which were identified after a thorough analysis of the majority of these papers which were determined. The investigation was assisted by the inclusion of the 38 papers that were deemed pertinent. Following published standards for reporting systematic reviews and meta-analyses (PRISMA), the current systematic review was carried out. Results: The researcher studied cross-sectional analytical, pre-experimental, and quasi-experimental studies with an intervention and a control group. The sample size ranged from 13 papers and 46 to 1294 participants.